2021
DOI: 10.3390/genes12081163
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Using Whole-Genome Sequence Data for Fertility, Health Indicator, and Endoparasite Infection Traits in German Black Pied Cattle

Abstract: This genome-wide association study (GWAS) aimed to identify sequence variants (SVs) and candidate genes associated with fertility and health in endangered German Black Pied cattle (DSN) based on whole-genome sequence (WGS) data. We used 304 sequenced DSN cattle for the imputation of 1797 genotyped DSN to WGS. The final dataset included 11,413,456 SVs of 1886 cows. Cow traits were calving-to-first service interval (CTFS), non-return after 56 days (NR56), somatic cell score (SCS), fat-to-protein ratio (FPR), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…We also detected several genomic regions with significant selection signals on BTA11 (11:31.25–38.71 Mb) and BTA13 (13:25.80–44.95 Mb). In gene annotation study of these regions, several candidate genes have been found related to reproductive system function in cattle, including Follicle Stimulating Hormone Receptor ( FSHR ) ( Widmer et al, 2021 ), KIAA1217 ( Mohammadi et al, 2020 ), Rho GTPase Activating Protein 21 ( ARHGAP21 ) ( Wolf et al, 2021 ), Myosin IIIA ( MY O 3A ) ( Mohammadi et al, 2020 ), and Glutamate Decarboxylase 2 ( GAD2 ) ( Mohammadi et al, 2020 ). Fertility is an essential element in beef cattle production because it directly relates to producing the offspring necessary to offset costs in production systems ( Thundathil et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also detected several genomic regions with significant selection signals on BTA11 (11:31.25–38.71 Mb) and BTA13 (13:25.80–44.95 Mb). In gene annotation study of these regions, several candidate genes have been found related to reproductive system function in cattle, including Follicle Stimulating Hormone Receptor ( FSHR ) ( Widmer et al, 2021 ), KIAA1217 ( Mohammadi et al, 2020 ), Rho GTPase Activating Protein 21 ( ARHGAP21 ) ( Wolf et al, 2021 ), Myosin IIIA ( MY O 3A ) ( Mohammadi et al, 2020 ), and Glutamate Decarboxylase 2 ( GAD2 ) ( Mohammadi et al, 2020 ). Fertility is an essential element in beef cattle production because it directly relates to producing the offspring necessary to offset costs in production systems ( Thundathil et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Out of the significant SNPs, 14 were located near 12 known genes, including AKAP8, CLHC1, MEGF10, SATB2, GATA6, SPATA6, COL12A1, EPS8, LUZP2, RAMAC, IL12A and ANKRD55. On chromosome 7, the rs42228650 SNP was close to MEGF10, a gene that was found to be associated with SCS in dairy cows in a previous investigation [48] and was considered as a candidate gene associated with residuals for fecal egg counts of gastrointestinal nematodes in German Black Pied cattle in a recent study [54]. On the same chromosome, two significant SNPs (AX-106741653 and AX-115114947) in the RB breed were located close to the AKAP8 gene, which was associated with somatic cell count in seven different populations of dairy cows in a complex study that used the combined approach of examining previous results from differential gene expression analysis and GWAS studies to identify the key pathways and candidate genes that potentially confer genetic resistance to mastitis in dairy cows [48].…”
Section: Discussionmentioning
confidence: 99%
“…Not all those traits, however, are yet fully described in DSN and genetic variants affecting those traits are unknown. So far, studies on milk production ( Korkuć et al, 2021 ), mastitis resistance ( Meier et al, 2020 ), endoparasites infection resistance ( May et al, 2019 ), and fertility traits ( Wolf et al, 2021 ) identified some candidate variants and genes affecting those traits. To improve the identification of DSN-typical DNA variants underlying the phenotypic variance, a customized SNP chip was designed for DSN ( Neumann et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%